Quality Of Worklife, Organizational Citzenship Behaviour dan Disiplin Kerja terhadap Kinerja Dosen - Badaruddin Badaruddin (Jurnal Mirai Management, 2021)
This study aims to examine the effect of quality of work life, Organizational Citizenship Behavior (OCB) and work discipline on the performance of the Indonesian Nobel Institute of Technology and Business lecturers. This study uses quantitative methods, namely data collection techniques obtained from the results of questionnaires distributed to examine the effect of Quality Of Work Life (QWL), Organizational Citizenship Behavior (OCB), and Work Discipline on Lecturer Performance. The population of this study were 108 lecturers Institute of Technology and Business Nobel Indonesian consisting of 39 undergraduate lecturers, 69 master's lecturers. To test the relationship between the independent variable and the dependent variable in this study, multiple linear regression analysis was performed. The results showed that Quality of Work Life (QWL), Organizational Citizenship Behavior (OCB) and work discipline had a positive and significant effect on lecturer performance in Institute of Technology and Business Nobel Indonesian. Keywords: Quality of Work Life (QWL), Organizational Citizenship Behavior (OCB), Work Discipline, Lecturer Performance.